(untitled) (Mustansiria Dental Journal, 2018)
The application of laser is widely used in many branches of medicine and surgery. The high energy laser has coagulating, cauterizing and destructive effect, while the low energy laser has a bio- stimulating effect. A hole was made using a surgical bur in zygomatic bone of four rabbits and a low energy laser was applied on zygomatic bone of experimental group and compared to control non- irradiated group. This study showed that application of low-energy laser has a promoting effect and facilitate bone deposition in the bony defect of the experimental group when compared to control group. It may be concluded that application of low-energy laser have promoting effect on acceleration of bone healing.